Measurements of chemical potentials in Pb-Pb collisions at √sNN = 5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Nath, Abhishek; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (Physical review letters, 2024)
This Letter presents the most precise measurement to date of the matter-antimatter imbalance at midrapidity in Pb-Pb collisions at a center-of-mass energy per nucleon pair √𝑠NN=5.02 TeV. Using the Statistical Hadronization framework, it is possible to obtain the value of the electric charge and baryon chemical potentials, 𝜇𝑄=−0.18±0.90 MeV and 𝜇𝐵=0.71±0.45 MeV, with unprecedented precision. A centrality-differential study of the antiparticle-to-particle yield ratios of charged pions, protons, Ω baryons, and light (hyper)nuclei is performed. These results indicate that the system created in Pb-Pb collisions at the LHC is on average baryon-free and electrically neutral at midrapidity.
Im Titel ist NN tiefgestellt
Gesehen am 05.05.2025
ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Bórquez Carcamo, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, F. Schlepper, J.J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, B. Windelband, A. Yüncü, F. Zanone, [und 1036 weitere]